Urbanization, inequality, and poverty in the People's Republic of China - Yuan Zhang (Asian Development Bank Institute (ADBI), 2016)
Relying on the present literature, official statistics, and household survey data in the People's Republic of China, this paper summarizes research findings on the relationship between urbanization, urban-rural inequality, and poverty, and provides further empirical evidence on the role of urbanization and government policies in urban poverty. Several conclusions can be drawn from. First, urbanization has a significant effect on reducing both poverty of rural residents and poverty of migrating peasants, and, consequently, has a positive effect on narrowing the rural-urban income or consumption gap. Urban labor markets play an important role in this effect. Second, urbanization is positively correlated with urban poverty. This can be explained by the competition between migrating peasants and urban workers in the labor market, and the failure of the government's anti-poverty policies in urban areas. Third, the existence of an informal sector has a negative effect on the poverty of urban citizens. Being employed by the informal sector significantly increases the probability of falling into poverty for urban citizens. Fourth, the minimum wage has a positive effect on reducing urban poverty, while the effect of other policies, such as Di Bao and the minimum living standard, is limited.
Keywords: I32; D63; R23; J42; 330; Inequality; poverty; urban; rural; labor market; urbanization; PRC; migration; households; peasants; workers; minimum wage; living standard; income; government policy; income gap